Prevalence of Psychological Violence in Young People in the South of Spain: Implications for Prevention - Lledó-Rando, María del Carmen; Perles-Novas, Fabiola; San-Martín-García, Jesús Emilio (PsychOpe, 2023)
The present study shows the prevalence of psychological violence received across ten dimensions in young people aged 18 to 25 years (55.8% female) and the perception of severity, in order to design more effective dating violence prevention programs. We used a sample taken in southern Spain of 771 people. The instrument used was an adaptation of Perceived Gender Violence Scale (VGP), a perception of dating violence scales towards women through 47 behaviours. It was adapted to assess psychological violence received in men and women, maintaining psychometric properties from original (α > .94) and a factor analysis without rotation resulting in a KMO-Barlett .94. The results show that 84.4% of women and 80.2% of men have received some type of psychological violence behaviour from their last partners. The most frequent are Affective indifference (67.7%), Discrediting (51.8%) and Control (50.6%), followed by Emotional manipulation and Sexual pressure. Differences were found by age, with more frequent at the age of 20 years old. Differences were found by sex in the type of psychological violence received, but the most important predictor variables were having a current partner (β = 17.7; p < .001; R2 = .07): where women with a partner perceive a lower level of violence received. The data suggest that it is necessary to incorporate these behaviours to be developed as contents in prevention programs; the research provides the most frequent behaviors
Keywords: Violencia de género en adolescentes; Violencia en la pareja - Aspectos psicológicos; Psychology violence; Gender-based violence; Intimate partner violence; Youth; Prevention; Affective indifference; Dating violence